TINJAUAN YURIDIS DISKRESI PEJABAT PUBLIK DALAM PENYELENGGARAAN PEMERINTAHAN - Widha Sinulingga (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2018)
Policy (discretion) is needed to overcome rapid changes. In theapplication of discretion of public officials, it is often considered to violate thelaw and be identified as criminal. While on the other hand, this kind of policyis needed, in times of emergency, so that it makes a blunder of officials. Thispaper attempts to look at how the legal position of discretion in governmentadministration is. The results of this writing are that the legal position ofdiscretion in the administration of government is an "exception" from theprinciple of legality (wet matigheid van bestuur), which means that the stateadministration is given the freedom to and on its own initiative to carry outactions to resolve certain urgent problems and the settlement rules do not yetexist, namely that they have not been made by the state body that is formallyassigned to formulate legislation.